2011
DOI: 10.5688/ajpe75581
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Performance in the First-Year of Pharmacy School

Abstract: Objectives. To determine the predictive validity of the Pharmacy College Admission Test (PCAT) scores and other variables for students' success in the first year of doctor of pharmacy (PharmD) programs. Methods. PCAT scores, entering grade-point averages (GPAs), demographic characteristics, and GPAs for the first year of pharmacy curriculum were collected from the Pharmacy College Application Service (PharmCAS) and from 22 pharmacy programs. Results. PCAT scores and entering GPAs were positively correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…Finally, as noted in a study of predictors of first-year pharmacy school performance, restriction of range is a persistent limitation for studies examining the correlation between admission variables and achievement. 32 The Pearsonproduct moment correlation is sensitive to restrictions of range in the values of variables. In the present study, correlations could be underreported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as noted in a study of predictors of first-year pharmacy school performance, restriction of range is a persistent limitation for studies examining the correlation between admission variables and achievement. 32 The Pearsonproduct moment correlation is sensitive to restrictions of range in the values of variables. In the present study, correlations could be underreported.…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that students most successful in the first year of pharmacy school had prepharmacy cumulative GPAs of 3.5 and higher PCAT scores in all subsets except problem-solving, compared with students placed on academic probation. 32 Our study was conducted at a school of pharmacy within a public university serving more than 14,000 undergraduate, graduate, and professional students. The University of Missouri-Kansas City (UMKC) School of Pharmacy was established in 1885 and educates over 500 students per year using 2 campuses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other studies indicate the PCAT is a moderate to strong predictor of grades earned in pharmacy programs. [4][5][6] Other studies show that PCAT subtest scores are more predictive than the PCAT composite score of first-year GPA. [7][8][9] In addition to the PCAT, other predictors of academic success in the pharmacy programs are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Hardigan et al reported that faculty interview score was a significant predictor of first-year GPA, while Kidd et al reported that faculty interview score was not a predictor of first-through third-year GPA. 4,8 Other studies evaluating admissions criteria also have conflicting results, such as those evaluating the predictive ability of cumulative prepharmacy GPA, 4,6,8,[11][12][13][14][15] and prior work experience. 16,17 Briceland and Hamilton reported that students with previous pharmacy work experience and higher first-year GPAs had higher third-year (P3) experiential GPAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation